Pendapatan Non-Halal, Zakat, Dewan Pengawas Syariah dan Reputasi Perbankan Syariah di Indonesia - Indria Puspitasari Lenap; Nina Karina Karim; Elin Erlina Sasanti (JAS (Jurnal Akuntansi Syariah), 2021)
This study examines the influence of non-halal funds, zakat, and the number of Sharia Supervisory Board (SSB) on the reputation of Islamic banking in Indonesia. The sample is determined by the purposive sampling method and resulted in 7 banks or 35 observations from 2014 to 2018. The results showed that non-halal funds did not affect the reputation of Islamic banking. However, non-halal funds in the company's financial report notes show that Islamic banks, especially in Indonesia, have not fulfilled sharia regulations. The results also showed that zakat affects the reputation of Islamic banking. Zakat in Indonesia is greatly influenced by company size in terms of its assets. Zakat paid by Islamic banks in Indonesia is still low, and the gap for the welfare of the directors and employees of Islamic banks is a huge difference. Furthermore, this study indicated that the number of SSB affects the reputation of Islamic banking. Therefore, SSB has a significant role in compiling reports about sharia compliance. The ideal number of SSB is between 3 and 6 people.